Elizabeth Singer Rowe and the Development of the English Novel - Backscheider, Paula R. (Johns Hopkins University Press, 2013)
Elizabeth Singer Rowe played a pivotal role in the development of the novel during the eighteenth century.Winner of the CHOICE Outstanding Academic Title of the Choice ACRLElizabeth Singer Rowe and the Development of the English Novel is the first in-depth study of Rowe's prose fiction. A four-volume collection of her work was a bestseller for a hundred years after its publication, but today Rowe is a largely unrecognized figure in the history of the novel. Although her poetry was appreciated by poets such as Alexander Pope for its metrical craftsmanship, beauty, and imagery, by the time of her death in 1737 she was better known for her fiction. According to Paula R. Backscheider, Rowe's major focus in her novels was on creating characters who were seeking a harmonious, contented life, often in the face of considerable social pressure. This quest would become the plotline in a large number of works in the second half of the eighteenth century, and it continues to be a major theme today in novels by women.Backscheider relates Rowe's work to popular fiction written by earlier writers as well as by her contemporaries. Rowe had a lasting influence on major movements, including the politeness (or gentility) movement, the reading revolution, and the Bluestocking society. The author reveals new information about each of these movements, and Elizabeth Singer Rowe emerges as an important innovator. Her influence resulted in new types of novel writing, philosophies, and lifestyles for women. Backscheider looks to archival materials, literary analysis, biographical evidence, and a configuration of cultural and feminist theories to prove her groundbreaking argument.